Pathogen delivery route impacts disease severity in experimental Mycoplasma ovipneumoniae infection of domestic lambs - Bryan Tegner Jacobson; Jessica DeWit-Dibbert; LaShae Zanca; Sobha Sonar; Carol Hardy; Michael Throolin; Patricia C. Brewster; Kaitlyn Andujo; Kerri Jones; Jonathon Sago; Stephen Smith; Lizabeth Bowen; et al. (Veterinary Research)
Abstract M. ovipneumoniae is a respiratory pathogen that can cause mild to moderate pneumonia and reduced productivity in domestic lambs. However, studies on both natural and experimental M. ovipneumoniae infection have reported highly variable clinical signs and pathology. Here, we assessed the impact of administering M. ovipneumoniae to the upper respiratory tract (URT) or to the lower respiratory tract (LRT) of two-month-old specific pathogen-free lambs. Lambs were inoculated with PBS (control) or with ceftiofur-treated nasal wash fluid obtained from sheep with natural M. ovipneumoniae infection, monitored for eight weeks, and subsequently euthanized. All lambs in the URT and LRT groups developed a stable infection with M. ovipneumoniae. M. ovipneumoniae infection led to lower weight gains and mild respiratory disease, with significantly greater effects following LRT inoculation compared to URT inoculation. At necropsy, lambs inoculated via the LRT showed consolidation of the cranial lung lobes. In addition, histological signs of  alveolar, bronchiolar, and interstitial inflammation were significantly more severe in the LRT compared to the URT group. M. ovipneumoniae loads in the trachea and bronchi also were significantly higher after LRT than URT inoculation. Interestingly, 9/10 inoculated lambs also tested positive for M. haemolytica in nasal swab but not in bronchial swab samples. In summary, our study suggests that bypassing protective mechanisms of the URT by delivering respiratory pathogens to the LRT leads to more severe respiratory disease and lung damage than delivery to the URT.